Effects of chronic stress on reinstatement of palatable food seeking: sex differences and relationship to trait anxiety - Ball, Kevin T. (Physiol Behav, 2020)
Previous research in our lab has established a causal role for chronic stress exposure in subsequent increases in relapse-like behaviors in male rats with a history of palatable food self-administration. Given that many of the neurobehavioral consequences of stress are sex dependent, we aimed to determine whether sex differences exist with regard to the effects of chronic stress on relapse. Additionally, because high trait anxiety confers vulnerability to stress-related disorders, we examined whether individual differences in trait anxiety were related to differences in relapse-like behavior after chronic stress exposure. Following elevated plus maze testing for classification into high- or low-anxiety phenotypes, male and female rats responded for highly palatable food pellets. During subsequent extinction training, stress was manipulated (0 or 90 min restraint/day for 7 days). Rats were then tested for cue- and pellet priming-induced reinstatement of palatable food seeking. Results showed that female rats displayed higher levels of responding during cue-induced reinstatement tests compared to males, and that a history of chronic stress caused an attenuation of cue-induced reinstatement in female, but not male, rats. Regarding pellet priming-induced reinstatement, there was a three-way interaction such that neither stress history nor anxiety phenotype was related to reinstatement in females, but a history of stress in males caused increased and decreased responding in low- and high-anxiety rats, respectively. These results suggest that biological sex and trait anxiety level may help to explain differences in vulnerability to relapse among individuals exposed to chronic stress. Such information may be useful in designing more personalized and effective treatments for obesity and eating disorders.